Knockout of hexokinase 2 regulates mitochondrial dysfunction and activates the NLRP3 signal pathway in the rumen epithelial cells of dairy cows - Yang, Tianyu; Lu, Zhiqi; Song, Han; Chen, Yuhang; Jiang, Maocheng; Zhan, Kang; Zhao, Guoqi (International journal of biological macromolecules, 2025)
Hexokinase 2 (HK2) plays a vital role in mitochondrial homeostasis; however, the molecular mechanisms underlying its involvement in high-concentrate diet-induced damage in the ruminal epithelium of dairy cows are poorly understood. This study aimed to explore the regulatory role of HK2 in mitochondrial function and responses to inflammation in the rumen of dairy cows fed a high-concentrate diet. Our results showed that, compared with a low-concentrate (LC) diet, feeding a high-concentrate (HC) diet increased oxidative stress and reduced relative antioxidant gene expression levels and enzyme activities in the ruminal epithelium. Furthermore, the expression of genes related to mitochondrial biosynthesis and structure decreased in the HC group, concomitant with nuclear oligomerization domain (NOD)-like receptor 3 (NLRP3) signaling pathway activation, which compromised normal rumen epithelium function. Meanwhile, transcription results showed the same trend in HK2-knockout bovine rumen epithelial cells (HK2KO BRECs) related to wild-type (WT) BRECs. Notably, the knockout of HK2 aggravated mitochondrial dysfunction, resulting in the impairment of mitochondrial morphology and quality, a reduction in mitochondrial membrane potential (MMP), mitochondrial permeability transition pore (MPTP) opening, increased reactive oxygen species (ROS) generation, and decreased expression of antioxidant genes. These changes led to upregulating genes and proteins in the NLRP3 pathway and activating proinflammatory response. In addition, metabolomic results showed that knockout HK2 altered the glycerophospholipid metabolic pathway. This study provides new strategies for mitigating high-concentrate diet-induced injury in the ruminal epithelium of dairy cows.